NMR Imaging of low pressure, gas-phase transport in packed beds using hyperpolarized xenon-129 - Pavlovskaya, Galina E.; Six, Joseph S.; Meersman, Thomas; Gopinathan, Navin; Rigby, Sean P. (Wiley, 2015)
Gas-phase magnetic resonance imaging (MRI) has been used to investigate heterogeneity in mass transport in a packed bed of commercial, alumina, catalyst supports. Hyperpolarized 129Xe MRI enables study of transient diffusion for micro- scopic porous systems using xenon chemical shift to selectively image gas within the pores, and, thence, permits study of low-density, gas-phase mass-transport, such that diffusion can be studied in the Knudsen regime, and not just the molecular regime, which is the limitation with other current techniques. Knudsen-regime diffusion is common in many industrial, catalytic processes. Significantly, larger spatial variability in mass transport rates across the packed bed was found compared to techniques using only molecular diffusion. It has thus been found that that these heterogeneities arise over length-scales much larger than